Government and not-for-profit accounting concepts and practices - Granof, Michael H.; Khumawala, Saleha B.; Calabrese, Thad D.; Smith, Daniel L. 1980- (Wiley, 2019)
Government and Not-for-Profit Accounting highlights the dynamic nature and constant evolution of the field and the intellectual challenges it presents. Designed to assist both preparers and potential users of financial reports, this book emphasizes concepts over rules and regulations to help students think critically and consider the effectiveness of alternate methodologies. Real-world examples demonstrate the similarities and differences between the public and private sectors—and how each might approach the same issue—and complete coverage of relevant reporting standards and practices aligns with the latest GASB, FASB, and AICPA changes.